2019
DOI: 10.2136/vzj2019.04.0039
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Atterberg Limits of Fine‐Grained Soils by Visible–Near‐Infrared Spectroscopy

Abstract: Two methods each to measure each Atterberg limit (SL, PL, and LL) were evaluated. A Vis‐NIRS technique successfully estimated Atterberg limits for fine‐grained soils. The Atterberg limits correlated with typical clay signatures in the Vis‐NIR spectrum Vis‐NIRS model performance was independent of the method used to generate the reference data. The Atterberg limits (shrinkage limit [SL], plastic limit [PL], and liquid limit [LL]) describe the physico‐mechanical behavior of soils and thus are crucial for civil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Besides the mentioned conventional methods, some researchers tried to find new methods for determining these values. For example, Rehman et al [40] studied visible-near infrared spectroscopy(Vis-NIRS) for identifying these indices. In the current study, the fall cone method and threading by hand have been utilised to determine the liquid limit and plastic limit, respectively.…”
Section: Materials and Testing Methodsmentioning
confidence: 99%
“…Besides the mentioned conventional methods, some researchers tried to find new methods for determining these values. For example, Rehman et al [40] studied visible-near infrared spectroscopy(Vis-NIRS) for identifying these indices. In the current study, the fall cone method and threading by hand have been utilised to determine the liquid limit and plastic limit, respectively.…”
Section: Materials and Testing Methodsmentioning
confidence: 99%
“…On the basis that for large sample quantities the conventional laboratory measurement methods are tedious and costly, some researchers have proposed new microstructural and mineralogical based testing methods for consistency limits determinations. For instance, Rehman et al [83] developed visible-near-infrared (vis-NIR) spectroscopy based models, correlating the Atterberg limits with typical clay signatures in the vis-NIR spectrum (from 400 to 2500 nm), reportedly obtaining very good and quite good estimation accuracies for LL and PL determinations, respectively, attributable to a strong correlation between them and spectrally active components related to soil clay mineralogy (mainly O-H bonds and Fe oxides). From field spectroscopy investigations of forest soils in Iran, Mousavi et al [84] reported that partial least-square regression modeling for the parameters of LL and I P in the raw spectra and the first derivative of the spectrum is very suitable, but is weak and not acceptable for PL determination.…”
Section: Recent Developments Regarding Consistency Limits Determinations and Soil Classificationmentioning
confidence: 99%
“…Therefore, there is a need to identify a scientific approach to determine the liquid limit and plastic limit of clays through a direct measurement without depending on the operator's judgement within a comparatively shorter timescale. Some recent developments have been made to find an alternative to the Atterberg limit estimation by the utilisation of spectroscopy [23,24], data-driven prediction models developed by artificial intelligence [25,26], and hygroscopic water content [27], to name a few. However, the consideration of spectroscopy may not seem an ideal solution in the geotechnical industry if there is a lack of understanding of electromagnetic radiation, wavelengths, and associated functional ability.…”
Section: Introductionmentioning
confidence: 99%